2022
DOI: 10.7759/cureus.29919
|View full text |Cite
|
Sign up to set email alerts
|

Emphasis on the Optimal Functional Recovery Through a Structured Inpatient Rehabilitation Program Along With a Home Exercise Regime in an Individual With Miller-Fisher Syndrome: A Case Report

Abstract: Guillain-Barre syndrome (GBS) is a rare inflammatory demyelinating polyradiculoneuropathy characterized by motor impairment, progressive, ascending, symmetrical flaccid limb paralysis, areflexia or hyporeflexia, and with or without cranial nerve involvement, which are the hallmark clinical indications of GBS, which can last over weeks to months. Miller-Fisher syndrome (MFS) is a post-infectious localized variant of GBS that includes ophthalmoplegia, ataxia, and areflexia, and is often associated with lower cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…GBS is distinguished by areflexia or hyporeflexia, progressive, ascending, symmetrical flaccid limb paralysis, and involvement of one or more cranial nerves. These symptoms can develop over a period of days to several weeks 10 . When compared to the aforementioned clinical manifestations, the patient in this study had clinical manifestations like generalized body weakness that affected both the lower and upper extremities (they were unable to move their legs or their hands as they normally would), tingling in the hands and feet, the inability to walk if unassisted, and difficulty swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…GBS is distinguished by areflexia or hyporeflexia, progressive, ascending, symmetrical flaccid limb paralysis, and involvement of one or more cranial nerves. These symptoms can develop over a period of days to several weeks 10 . When compared to the aforementioned clinical manifestations, the patient in this study had clinical manifestations like generalized body weakness that affected both the lower and upper extremities (they were unable to move their legs or their hands as they normally would), tingling in the hands and feet, the inability to walk if unassisted, and difficulty swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Ataxia, ophthalmoplegia, paradoxical hyperreflexia, and alternate consciousness are all symptoms of Bickerstaff brainstem encephalitis. Fisher's syndrome has been associated with antibodies to ganglioside Q1b [2]. An upper respiratory or digestive tract disorder frequently comes before this severe polyneuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Guillain-Barre syndrome (GBS) is unusual inflammatory demyelinating polyradiculoneuropathy that results from loss of motor control. The most common forms responsible for 70-80% of cases are acute motor axonal neuropathy (AMAN) and acute inflammatory demyelinating neuropathy (AIDP), and others are Miller-Fisher syndrome (MFS) and acute axonal and sensory axonal neuropathy (AMSAN), which are the variants of GBS [1]. Numerous clinical, neurophysiological, and pathological studies have suggested that acute inflammatory neuropathy primarily affects large-diameter myelinated nerves.…”
Section: Introductionmentioning
confidence: 99%